Perilous desert : insecurity in the Sahara - Wehrey, Frederic M.; Boukhars, Anouar (Washington, DC : Carnegie Endowment for International Peace, 2013)
The geopolitical significance of the Sahara is becoming painfully clear. Islamist militant groups and transnational criminal networks are operating in the region's most fragile states, exploiting widespread corruption, weak government capacity, crushing poverty, and entrenched social and ethnic tensions. The unrest spills over borders and aggravates protracted regional crises. This insecurity raises urgent concerns for the broader Sahara and the West. Perilous Desert details the sources of instability and what can be done to minimize the threat of simmering conflicts. L.
Foreword / Marwan Muasher -- Introduction / Frederic Wehrey -- The struggle for security in east Libya / Frederic Wehrey -- Borderline chaos? stabilizing Libya's periphery / Peter Cole -- Organized crime and conflict in the Sahel-Sahara region / Wolfram Lacher -- The paranoid neighbor: Algeria and the conflict in Mali / Anouar Boukhars -- The drivers of insecurity in Mauritania / Anouar Boukhars -- Mauritania's Islamists / Alex Thurston -- Simmering discontent in the western Sahara / Anouar Boukhars.
Online resource; title from digital title page (viewed on Apr 17, 2013).
Includes bibliographical references and index.
JSTOR
Keywords: Security, International -- Sahara; Security, International -- Sahel; HISTORY -- Military -- Other; TECHNOLOGY & ENGINEERING -- Military Science; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; Security, International; Africa -- Sahel; Sahara